Microbiological Quality Assessment by PCR and Its Antibiotic Susceptibility in Mangrove Crabs (Ucides cordatus) from Guanabara Bay, Rio de Janeiro, Brazil - M. C. N. Carvalho; M. M. Jayme; G. S. Arenazio; F. V. Araújo; S. G. F. Leite; E. M. Del Aguila (International Journal of Microbiology)
The bacteriological quality of crabs from three different mangroves (Itaóca, Suruí, and Piedade) from Rio de Janeiro state, Brazil, was investigated using conventional and molecular methods. The results revealed high counts for total coliforms in meat and hepatopancreas samples. PCR analyses identified 25 Escherichia coli colonies in the Itaóca, Piedade, and Suruí samples, detecting 13 enterotoxigenic colonies and 9 enteroaggregative colonies. Respectively, 12, 11, and 21 Vibrio parahaemolyticus strains were detected in the Itaóca, Piedade, and Suruí samples. Two V. cholerae strains were detected in the Piedade samples. The E. coli strains isolated in the present study showed resistance to gentamicin. E. coli strains from the Piedade samples showed 33% resistance to chloramphenicol and the strains also showed multiresistance to several antimicrobial agents with a MAR index ranging from 0.12 to 0.31. Vibrio strains from Piedade, Itaóca, and Suruí showed 86%, 78%, and 85% resistance, respectively, to ampicillin. The isolated Vibrio strains showed multiresistance to several antimicrobial agents, with a MAR index ranging from 0.12 to 0.25. The presence of these organisms in crab meat is an indication of microbial contamination, which may pose health risks to consumers when improperly cooked.